Ecological Citizenship: The Role of Young Citizens in Environmental Responsibility and Sustainability - Bria, Makarius Erwin; Komalasari, Kokom; Sundawa, Dadang; Mahpudz, Asep (ASANKA : Journal of Social Science and Education, 2025)
This article examines ecological citizenship, which refers to individual awareness and responsibility as part of the larger natural environment, and is becoming increasingly important in the context of global climate change and the current environmental crisis. Being environmentally conscious is important for young citizens because they will inherit this planet in the future. The method used in this research is qualitative research with library research. Data was collected from an analysis of relevant source books and journals and a document analysis of several articles related to this topic. Citizenship Education plays an essential role in shaping ecological citizenship. Citizenship education develops attitudes of care, civic responsibility, commitment, and engagement for young citizens to act positively to protect the environment. Further research needs to be conducted to explore the most effective learning strategies in instilling the values of ecological citizenship, both through conventional methods and digital technology-based approaches. Young people are expected to understand the concept of environmental citizenship and actively participate in concrete actions.